Implementation of Smart Tourism in Payungi Market Metro Lampung City - Utaridah, Nanda; Frasetya, Vito; Wibawa, Agung; Gautama, sidharta Adi (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2024)
Visitors to the culinary tourism at Payungi Market in Metro City are increasing, since Payungi Market has implemented smart tourism, which is an approach that utilizes information and communication technology in the tourism industry. This approach aims to improve efficiency, accessibility and experience for tourists. Payungi Market uses communication technology such as mobile applications, websites, Instagram social media, and geographic information systems, to simplify information and facilitate interactions with tourists. This research is qualitative research with descriptive methods. The aim of this method is to find out how to apply the smart tourism concept and its use. This research data was collected through observations on social media, research locations and literature studies from both domestic and foreign journals. The research results show that the payungi market has succeeded in achieving the three elements in the smart tourism concept, namely Smart experience, Smart business ecosystem and Smart destination, which aims to increase culinary promotion, excellent service and social and business facilities through creative, interesting and useful information for people so they can participate, do things and experiences that have value for themselves.